RUQYAH MANDIRI DI KALANGAN KELAS MENENGAH: STUDI LIVING QUR'AN DI PONDOK PESANTREN MU'ALLIMIN AMBULU JEMBER - Ifah, Alif Wiladatil; Qurrotul Aini, Siti (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2024)
Ruqyah independently at Al-Muta'allimin Islamic Boarding School is a form of living Qur'an in the form of tradition in society and the majority are attended by worshipers from the middle class. The focus of this research is (1) How is the process of implementing ruqyah independently at the Al-Muta'allimin Islamic Boarding School? (2) What is the meaning of the middle class congregation towards ruqyah independently at the Al-Muta'allimin Islamic Boarding School? (3) What are the implications of independent ruqyah at the Al-Muta'allimin Islamic Boarding School for the middle class congregation? This research is a qualitative research with the type of field research, using Karl Manheim's sociology of knowledge theory. Data collection techniques using observation, interviews and documentation. The results of this study indicate that (1) The implementation of independent ruqyah is carried out every Kliwon Wednesday night at the Al-Muta'allimin Islamic Boarding School. The process began with reading the tawassul, then strengthening the belief by reading the arguments about ruqyah by Kiai Masduki and immediately reading the prayers and verses of the ruqyah. (2) The meaning of the middle class congregation towards independent ruqyah at Al-Muta'allimin Islamic Boarding School is based on Karl Manheim's Sociology of Knowledge theory, namely independent ruqyah as an escape to seek medicine and peace of mind from business development problems, education problems, self-control problems and worship problems. (3) The implications of independent ruqyah at the Al-Muta'allimin Islamic Boarding School for the middle class congregation are that they are more diligent in worship, the heart becomes more calm and peaceful.